Pengaruh Profitabilitas Dan Solvabilitas Terhadap Nilai Perusahaan PT Bank Rakyat Indonesia - Widia Rahmi Iskandar; Deri Apriadi (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the effect of profitability and solvency on firm value at PT Bank Rakyat Indonesia (Persero) Tbk during the 2015–2024 period. Profitability is measured by Return on Assets (ROA) and Return on Equity (ROE), while solvency is measured by the Debt to Equity Ratio (DER). Firm value is proxied by Price to Book Value (PBV). The analytical method used is multiple linear regression with secondary quantitative data obtained from BRI’s annual financial reports. The results indicate that, partially, ROA and ROE have a positive and significant effect on firm value, whereas DER has a negative but non-significant effect. Simultaneously, profitability and solvency both have a significant impact on firm value. These findings suggest that an increase in profitability is the primary factor in enhancing firm value, while solvency must be managed carefully so as not to diminish investors’ perceptions of the company’s financial risk.